Phase II Study of Pegylated Liposomal Doxorubicin and Carboplatin in Patients With Platinum-Sensitive and Partially Platinum-Sensitive Metastatic Ovarian Cancer. Issue 6 (1st July 2009) - Rapoport, B. L.; Vorobiof, D. A.; Slabber, C.; Alberts, A. S.; Hlophe, H. S.; Mohammed, C.
Abstract : Objective: This phase II study assessed the activity and safety of pegylated liposomal doxorubicin (PLD) plus carboplatin in relapsed ovarian cancer (ROC). Method: Forty women with platinum-sensitive and partially platinum-sensitive ROC were treated with PLD 50 mg/m 2 plus carboplatin area under the curve 5 every 28 days in this South African multicenter study. All patients who completed 3 cycles of chemotherapy were evaluated for response. Primary outcome was response in the intent-to-treat population. Results: Complete response was 35%, and partial response was 32.5% (overall response, 67.5%). Median time-to-progression was 11.9 months, and median survival was 30.0 months. Overall response was higher in platinum-sensitive (81%) versus partially platinum-sensitive patients (53%), as were median duration of response, median time-to-progression, and median survival. Treatment was well tolerated, with no grade 4 nonhematologic toxicities. Grade 3/4 hematologic toxicities included leukopenia (58%), neutropenia (55%), and thrombocytopenia (43%). Conclusion: Pegylated liposomal doxorubicin plus carboplatin is well tolerated and active in the treatment of platinum-sensitive and partially platinum-sensitive ROC.